Sistem Penunjukan Penjabat Kepala Daerah dalam Perspektif Teori Pengisian Jabatan - Syaiful Anwar, Muhammad; Sari, Rafiqa; Satrio, Ndaru (LPPM Universitas Harapan Bangsa, 2024)
The Regional Head is important in the implementation of the wheels of government. The government will stagnate if there is a vacancy of the regional head. The filling of acting regional heads has caused polemics. The absence of public participation in the selection of Acting Regional Heads by prioritizing appointments from the central government has actually increased the dominance of centralistic patterns. Therefore, this study aims to analyze whether the appointment of Acting Regional Heads by the Central Government is in accordance with the theory of filling positions, and how is the position of community legitimacy in the appointment of Acting Regional Heads based on regional autonomy? This research method uses normative juridical method. The result of this research is that the election of the Acting Regional Head must change the perspective of